Być akademikiem w uczelni wojskowej - Kojkoł, Jerzy (Humaniora. Czasopismo Internetowe, 2023)
Being an academic at a military academy, that is, one overseen by the Minister of National Defense, has a unique flavor. This can be understandable when one takes into account the historical and legal context. The an academic in a military university is associated with being a soldier and a scientist, a former soldier and a scientist, “our” civilian and a scientist, and simply a civilian scientist. However, each of them must always remember the authority of the Minister of Defense and National, although it does not predetermine the quality of his scientific work in the case when one is a scientist and not a collector of academic degrees.